Acceptability and feasibility of multiple micronutrient powders vs. iron syrup in young children in Bihar, India - Young, Melissa F.; Girard, Amy Webb; Mehta, Rushkan; Srikantiah, Sridhar; Menon, Purnima; Ramakrishnan, Usha; Martorell, Reynaldo; Avula, Rasmi (Wiley, 2017)
Nearly 80% of children under 5 are anemic in Bihar, India. Pediatric iron/folic‐acid syrup (IFAS) and multiple micronutrient powders (MMPs) are two of the evidence‐based interventions to prevent anemia. India's current policy solution includes IFAS for children, but there are limited data on the use and effectiveness of MMPs. We examined the acceptability and feasibility of IFAS versus MMPs, using a longitudinal randomized cross‐over design (NCT02610881). Informed consent was obtained from caregivers of children 6–23 mo (N=100) covered under two health centers (HCs) in West Champaran district, Bihar. In one HC, five trained Accredited Social Health Activists (ASHAs), a cadre of front line workers, delivered MMPs to 10 eligible households for one month, and then IFAS for one month. In the second HC, ASHA's delivered IFAS in the first month followed by MMPs. Crossovers were separated by a 2‐week washout. Per Government of India guidelines, ASHAs administered 1 ml IFAS via standardized and calibrated droppers to children twice per week. For MMPs, ASHAs delivered 30 sachets to families once with instructions to use one sachet per day and followed‐up after 2 weeks. Household surveys were conducted at baseline (N=100), midline (1 mo; N= 95) and endline (2 mo; N= 93). Focus group discussions and in‐depth interviews were held at baseline and endline with 10 participating ASHAs and 10 mothers per HC, respectively. For both products there was high compliance (> 80% reported taken as instructed) and high acceptability (> 90% consumed product and would continue using). Mothers reported IFAS and MMPs to be beneficial for their children (39% MMPs, 40% IFAS, 18% both, 2% neither), and to have few side effects (30% MMPs, 30% IFAS, 2% both, 38% neither). There was no significant preference for either product based on ease of use (42% IFAS, 31% MMPs, 25% both, 2% neither), preferred by the child (45% IFA syrup, 37% MMPs, 16% both, 2% neither), preferred by caregiver (44% IFAS, 34% MMPs, 19% both, 2% neither), and preference for continued use (38% IFAS, 37% MMPs, 24% both, 2% neither). ASHAs were willing to distribute either product but reported concerns about increased work load and need for incentives. Mothers and ASHAs indicated that the direct delivery of IFAS ensured that the child received and consumed the full dose whereas MMPs consumption depended on quantity of food consumed, especially among younger children. Preference for IFAS may also be related to a belief that the child would “waste less.” Another perceived advantage was that administration did not involve food. Our study highlights that IFAS and MMPs were highly acceptable for consumption by children and for delivery by ASHAs, thus offering additional policy options for preventing pediatric anemia, and emphasizing the need to integrate supplementation with the promotion of optimal infant and young child feeding practices.Support or Funding InformationFunding: Bill & Melinda Gates Foundation, through POSHAN, led by IFPRI